DETERMINANTS OF ACCESS TO CREDIT AMONG SMALLHOLDER RICE FARMERS IN WESTERN AGRICULTURAL ZONE OF BAUCHI STATE, NIGERIA - Dalhatu, A.; Garba M.; Abdullahi, S. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study examined the determinants of access to credit among smallholder rice farmers in western agricultural zone of Bauchi State, Nigeria. Multi-stage sampling techniques was used in selecting 209 respondents. Data were collected using questionnaires and analyzed using both descriptive and inferential statistics. The result revealed that majority (82.8%) of the respondents were male and (80.9%) were married with a mean age of 39years. (60.3%) engaged primarily in crop farming, with a mean of 6people in their household and cultivate an average of 5ha of land. The finding also revealed that 51.7% of the respondents relied on informal credit sources. The logistic regression result showed that farming experience had a positive significant influence on access to credit at (p<0.01), cooperative membership and access to extension services were positive and significant at (p<0.05) and years of membership had a negative significant influence at (p<0.05). Major constraints faced by the respondents were limited access to formal credit (73.2%), lack of collateral (67.9%) and inadequate information about available credit (64.1%). The study concludes that farming experience, cooperative membership, years of membership to cooperative and access to extension services were the determinants of access to credit in the study area. Based on the constraints highlighted the study recommends enhancing small-scale rice farmers access to formal credit through the strengthening of cooperative associations, adoption of alternative collateral systems, sensitization of farmers about credit opportunities through radio programs, extension agents and community meetings .